2021
DOI: 10.1111/1475-6773.13880
|View full text |Cite
|
Sign up to set email alerts
|

Patient selection in the Comprehensive Care for Joint Replacement model

Abstract: Objective: To understand whether the Comprehensive Care for Joint Replacement (CJR) program induces participating hospitals to (1) preferentially select lower risk patients, (2) reduce 90-day episode-of-care costs, (3) improve quality of care, and (4) achieve greater cost reduction during its second year, when downside financial risk was applied. Data sources: We identified beneficiaries of age 65 years or older undergoing hip or knee joint replacement in the 100% sample of Medicare fee-for-service inpatient (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Then, we used a difference-in-difference strategy (DID) to compare 90-day episode-of-care cost, quality of care, and patient selection between each group of CJR participants and nonparticipant hospitals (first CJR vs. non-CJR and second CJR vs. non-CJR) over the first 2 performance years (2016 and 2017). We paid close attention to changes in patient characteristics among elective admission because financial pressures between first and second CJR hospitals might lead to heterogeneous patient selection 13…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, we used a difference-in-difference strategy (DID) to compare 90-day episode-of-care cost, quality of care, and patient selection between each group of CJR participants and nonparticipant hospitals (first CJR vs. non-CJR and second CJR vs. non-CJR) over the first 2 performance years (2016 and 2017). We paid close attention to changes in patient characteristics among elective admission because financial pressures between first and second CJR hospitals might lead to heterogeneous patient selection 13…”
Section: Methodsmentioning
confidence: 99%
“…We paid close attention to changes in patient characteristics among elective admission because financial pressures between first and second CJR hospitals might lead to heterogeneous patient selection. 13 In addition to the DID approach, we also used a triple difference analysis (DDD) to determine whether the policy effects differed among second CJR compared with first CJR hospitals. A statistically significant DDD estimator would suggest that the effect of CJR differs between first and second CJR hospitals.…”
Section: Methodsmentioning
confidence: 99%
“…4 Additionally, the racial disparity gap in receipt of TKR appears to be growing for Medicare beneficiaries in recent years 5,6 By using models that do not adjust for varied social risks, hospitals may be incentivized to avoid socially disadvantaged, high-risk patients for TKR since hospitals are held accountable for additional costs following surgery. 7,8 This may be one contributor to the documented increasing racial disparities gap in utilization and offering of a TKR 5,6 Although studies have identified patient characteristics [9][10][11][12][13] and clinical factors 14,15 associated with PROs after joint replacement, few have evaluated the role of social risk factors in PROs after TKR. 16,17 Determining the relationship between social risk factors and post-TKR PROs is crucial to addressing unmet social needs and inequities in TKR patient selection 18,19 and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, today, the risk‐standardized model does not include social risk factors or the social determinants of health, 3 which population research has documented to contribute up to 80% of all factors that drive global health outcomes 4 . Additionally, the racial disparity gap in receipt of TKR appears to be growing for Medicare beneficiaries in recent years 5,6 By using models that do not adjust for varied social risks, hospitals may be incentivized to avoid socially disadvantaged, high‐risk patients for TKR since hospitals are held accountable for additional costs following surgery 7,8 . This may be one contributor to the documented increasing racial disparities gap in utilization and offering of a TKR 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, given that financial risk is shifted to the hospital system, bundled payment programs may provide an incentive for the selection of healthier and less-costly patients [5,6]. Thus far, various evaluations of the CJR program have included an 1155387H SSXXX10.1177/15563316231155387HSS Journal®: The Musculoskeletal Journal of Hospital for Special SurgeryKiani et al research-article2023 assessment of potential unintended consequences, and a recent study looking at Medicare data found that CJR hospitals preferentially avoided patients aged 85 years or older and patients identifying as black [14,15,23,27]. As changing incentives have the potential to negatively affect patients' access to care, continued monitoring of unintended consequences is warranted, both on the national level and in subgroups based on hospital type, geography, and patient characteristics.…”
Section: Introductionmentioning
confidence: 99%